ANALISIS PENGGUNAAN VARIASI BAHASA MADURA BANGKALAN PADA KOMUNIKASI INFORMAL SISWA KELAS VIII SMPN 1 KWANYAR BANGKALAN - Rifai, Ahmad; Febriani, Ika; Rosid, Abdul (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia)
In everyday life, humans need to interact with other people. Conversation is one form of such interaction. Conversations are formed by two or more people. Conversations that occur can be in the form of formal conversations or informal conversations. In the conversation carried out, the language varies from each individual from various regions. This study discusses the variety of language in terms of speakers in class VIII students of SMPN 1 Kwanyar Bangkalan Madura. The uniqueness of this study with other research is that this study discusses the existence of language variations that exist within the district area. Only from one district but able to produce many language variations. The purpose of this study was to describe the variety of language in terms of speakers in informal communication among class VIII students of SMPN 1 Kwanyar Bangkalan Madura. The approach in this research is descriptive qualitative. The data source of this research is the eighth grade students of SMPN 1 Kwanyar Bangkalan Madura. The data in this study were all utterances spoken by grade VIII students of SMPN 1 Kwanyar Bangkalan Madura. Data collection used observation techniques, proficient listening techniques, interview techniques, recording techniques, and note taking techniques. Data analysis techniques using data reduction methods, data presentation, and conclusions. The validity of the data used investigator triangulation. The results showed that in informal communication among eighth grade students of SMPN 1 Kwanyar, there were variations in the language in terms of speakers, there were variations in language based on dialect, idiosyncrasy, gender, and age.